2021
DOI: 10.1002/mds.28633
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Communication About End‐of‐Life Care in Atypical Parkinsonism

Abstract: Background Studies on preferences regarding discussions on end‐of‐life care (EOLC), advance care planning (ACP), medical assistance in dying (MAiD), and brain donation have not yet been conducted in patients with atypical parkinsonism (AP). Objective The aim of this study was to know the preferences of patients with AP regarding discussions on EOLC, ACP, MAiD, and brain donation. Methods This cross‐sectional study was conducted in patients clinically diagnosed with AP. An adapted questionnaire that assessed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…In a recent international multicenter study, concepts for palliative care interventions were studied and palliative care training programs were developed (Gatsios et al 2021 ; Meinders et al 2021 ). A survey on aPS patients revealed that this patient group prefers an early conversation about diagnosis with information about the disease, natural history, prognosis, and treatment options (Saranza et al 2021 ). These aPS patients also want to have a conversation about end of life and advance care planning in later stages of the disease (Saranza et al 2021 ).…”
Section: Clinical Care For Patients With Parkinson’s Disease and Atyp...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent international multicenter study, concepts for palliative care interventions were studied and palliative care training programs were developed (Gatsios et al 2021 ; Meinders et al 2021 ). A survey on aPS patients revealed that this patient group prefers an early conversation about diagnosis with information about the disease, natural history, prognosis, and treatment options (Saranza et al 2021 ). These aPS patients also want to have a conversation about end of life and advance care planning in later stages of the disease (Saranza et al 2021 ).…”
Section: Clinical Care For Patients With Parkinson’s Disease and Atyp...mentioning
confidence: 99%
“…A survey on aPS patients revealed that this patient group prefers an early conversation about diagnosis with information about the disease, natural history, prognosis, and treatment options (Saranza et al 2021 ). These aPS patients also want to have a conversation about end of life and advance care planning in later stages of the disease (Saranza et al 2021 ). Advance care planning concepts are necessary to improve clinical care (Lum et al 2019 ; Seeber et al 2019 ).…”
Section: Clinical Care For Patients With Parkinson’s Disease and Atyp...mentioning
confidence: 99%